2021
DOI: 10.1155/2021/5516928
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Organic and Inorganic Fertilizers on Growth and Nutrient Uptake by Young Cacao (Theobroma cacao L.)

Abstract: Sustainable cacao cultivation in Ghana has been seriously hampered by high seedling mortality due to the low soil fertility of lands used for the establishment of new cacao farms. Alleviating the low soil fertility to enhance sustainable cacao cultivation requires the use of fertilizers. A study was therefore conducted at the Cocoa Research Institute of Ghana to determine the effect of integrated application of poultry manure (PM) and sulphate of ammonia (SOA) fertilizers on survival, growth, and nutrient upta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 24 publications
2
5
0
2
Order By: Relevance
“…It was expected that the plant survival after P. cinnamomi inoculation would increase with Biohumin ® treatment, as reported for other inorganic and organic fertilisers [59,60]. In this study, it was observed that the plants fertilised with 12.5% Biohumin ® or not fertilised had higher survival rates than the plants fertilised with 25% Biohumin ® , across all the non-infested treatments.…”
Section: Survival Of Oak Seedlingssupporting
confidence: 73%
“…It was expected that the plant survival after P. cinnamomi inoculation would increase with Biohumin ® treatment, as reported for other inorganic and organic fertilisers [59,60]. In this study, it was observed that the plants fertilised with 12.5% Biohumin ® or not fertilised had higher survival rates than the plants fertilised with 25% Biohumin ® , across all the non-infested treatments.…”
Section: Survival Of Oak Seedlingssupporting
confidence: 73%
“…Because of that utilization of waste Agriculture, plantation cocoa worthy conducted because fertilizer organic capable increase production plant and improving fertility soil in the cultivation of cocoa (Young et al, 2021). Besides, the application of fertilizer organic and inorganic explained in the study Dogbatse et al (2021) mention integrated nutrients from soil marginal will be very useful for nutrition tree cocoa. Although N upgrade is available with SOA (Sulfur of Ammonium), the application of SOA (Sulfur of Ammonium) produces tree cocoa with TCSA (trunk cross-sectional area) smaller than other treatments that are changed with PM (poultry manure).…”
Section: Resultsmentioning
confidence: 99%
“…Applying fertilizer is a typical way that is used by farmers to maintain soil fertility through replenishing nutrient stocks and maintaning soil acidity [2]. Fertilization is one of the important inputs given to plants so that they can grow and develop properly [3]. At the time of fertilization, based on chemical compounds, fertilizers are divided into two, namely organic and inorganic fertilizers.…”
Section: Introductionmentioning
confidence: 99%